Drunkenness and intoxication: critical narratives about Edgar A. Poe and alcohol (Colloquia Comparativa Litterarum, 2025)
For almost two hundred years, the critical narrative presenting Edgar A. Poe’s use and misuse of alcohol has oscillated between two poles. On the one hand, mainly in the United States, his enemies, while he was still alive and soon after his death presented him as an alcoholic and a man of great talent, yet someone who deserved moral rebuke. On the other hand, Poe’s American admirers and his European modernist followers interpreted Poe’s relation with alcohol positively in two aspects. First, Poe’s drinking was a temporary escape from his miserable life in the American milieu of utilitarian and moralistic attitudes toward art. And, second, Poe was seen as a romantic and modernist artist finding in alcohol a path transcending reality and leading to the domain of pure art. The article studies the formation of the dual narrative of Poe’s drunkenness/intoxication in the United States and modernist France (and to a much lesser extent in Bulgaria and Russia). The study also sheds some light on Bulgarian criticism in both its popular and commercial version, as well as in its high modernist period presented by Bulgaria’s leading modernist and avant-garde artist Geo Milev (1895-1925). Bulgarian critics, when discussing Poe and alcohol, repeat in an impoverished fashion well-established American and European aspects of the narrative of Poe and alcohol.
Keywords: Edgar A. Poe; alcohol; Poe in the US; Poe in France; Poe in Bulgaria